Mechanical performance analysis and parametric study of double-deck plate-truss composite steel girders of a three-tower four-span suspension bridge. (15th November 2019) - Cheng, Jin; Xu, Mingsai; Xu, Hang
Highlights: The mechanical behaviour of double-deck plate-truss composite steel girders is studied. Two sub-systems of plate-truss composite steel girders are analyzed separately. Effects of various parameters on the girders' mechanical behaviour are studied. Abstract: A sufficient understanding of the mechanical performance of plate-truss composite steel girders is essential for practical design as such girders are utilized widely in long-span bridges worldwide. Using the Oujiang River North Estuary Bridge which is a three-tower four-span suspension bridge under construction in China as an example, this paper investigates the mechanical performance of two sub-systems Ⅰ and Ⅱ of double-deck plate-truss composite steel girders. System Ⅰ is the main bridge system, with the steel plate deck and the longitudinal ribs acting as a part of the main carrying members of the bridge. System Ⅱ is the stiffened steel plate deck consisting of the longitudinal ribs, diaphragms and the deck plate as their common upper flange, acting as a bridge floor. Three-dimensional finite element models (FEM) are developed and different load cases are considered for System Ⅰ and System Ⅱ in the analysis. The results show that 60–80% of total load is carried by the deck plate and longitudinal ribs in System Ⅰ, and the mechanical response of System Ⅱ is susceptible to live load. Finally, a parametric study is conducted to investigate the influences of various structural parameters on the mechanical performance of double-deck plate-truss composite steel girders. The obtained analytical results lead to a better understanding of the complex mechanical performance of steel deck-truss composite system, particularly with respect to stress distribution and load carrying mechanism.